The Utimate Hitchhiker's Guide to the Galaxy : Five Novels and One Story - Adams, Douglas, 1952-2001 (New York : Harmony Books, 2010)
This volumes brings together the six stories chronicling Arthur Dents travels across space and time.
Introduction: A guide to the guide -- The hitchhikers guide to the galaxy -- The restaurant at the end of the universe -- Life, the universe and everything -- So long, and thanks for all the fish -- Young Zaphod plays it safe -- Mostly harmless.
Keywords: Dent, Arthur -- (Fictitious character) -- Fiction; Prefect, Ford -- Fiction; Interplanetary voyages -- Fiction; Science fiction; Novels